Pengembangan Orientasi Pasar Dan Orientasi Kewirausahaan Terhadap Kinerja Pemasaran Usaha Kecil Dan Menengah (UKM) Di Provinsi Bengkulu - Novrianda, Herry; Shar, Aan; Arisandi, Debby (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2021)
The purpose of this study is to analyze and determine the development of market orientation and entrepreneurial orientation and their effects on the marketing performance of small and medium enterprises (SMEs) in Bengkulu Province. This research is a descriptive study with a quantitative approach. The sampling method used non probability with judgmental techniques (purposive) with a total sample of 270. The results showed that SMEs in Bengkulu Province had run their business with market orientation and entrepreneurial orientation in good categories. When viewed from the marketing performance, most of them have achieved a fairly good level of performance as well. For this reason, if we look at the influence between variables, market orientation and entrepreneurial orientation have a positive and significant effect at the marketing performance of SMEs in Bengkulu Province. This means that the better market orientation and entrepreneurial orientation, the better marketing performance for SMEs in Bengkulu Province. Thus, the hypothesis which states that market orientation and entrepreneurial orientation have a positive and significant effect on marketing performance for small and medium enterprises (SMEs) can be accepted